Διερεύνηση διαφυλικών διαφορών ως προς την εκδήλωση αγχωδών διαταραχών σε μαθητές της Ε’ και Στ’ Δημοτικού - Καρτέρης Βασίλειος; Αντωνίου Αλέξανδρος-Σταμάτιος (Πανελλήνιο Συνέδριο Επιστημών Εκπαίδευσης, 2017)
Anxiety disorders are the most common mental disorders in childhood and adversely affect the functioning of children in various important areas of their life. According to contemporary international research, girls seem to be more prone to the appearance of anxiety disorder. This survey was conducted on a sample of 461 pupils of grades E and F in urban and semi-urban areas of Greece and confirmed the findings of corresponding international studies. In particular, it was found that gender significantly affects the occurrence of specific phobia (fear of bodily injury), generalized anxiety disorder, panic-agoraphobia, social phobia and separation anxiety. Typically, girls appeared to have higher levels of anxiety in various events in their lives. It has been shown that early detection and early intervention, along with the strengthening of counseling parents, contribute significantly to the smooth psychosomal development of children with anxiety disorders.